"Doing a number": adaptation of political violence in the aftermath of the Northern Irish conflict. Issue 3 (2nd September 2018) - Uležić, Sanjin
ABSTRACT: Focusing on the contemporary iteration of the republican armed struggle in Northern Ireland this work posits that a scaled-down approach to the strategic outlook was developed by violent dissident republicans as a reaction to resource constraints and a post-conflict context. The adjusted strategic outlook became predicated on a strategy of provocation with the intent being to draw out some form of governmental response while maintaining a heightened state of emergency. As the post-conflict normalization in Northern Ireland represented a relatively easy target for the armed groups, this strategy of provocation could rely on rudimentary tactics, both violent and non-violent. This work concludes by exploring one such tactic that straddles the divide between the two, hoax devices, which have become a staple in the repertoire of violent dissident republicans.